2017
DOI: 10.1038/mi.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

The intraspecies diversity of C. albicans triggers qualitatively and temporally distinct host responses that determine the balance between commensalism and pathogenicity

Abstract: The host immune status is critical for preventing opportunistic infections with Candida albicans. Whether the natural fungal diversity that exists between C. albicans isolates also influences disease development remains unclear. Here, we used an experimental model of oral infection to probe the host response to diverse C. albicans isolates in vivo and found dramatic differences in their ability to persist in the oral mucosa, which inversely correlated with the degree and kinetics of immune activation in the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
157
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(182 citation statements)
references
References 59 publications
15
157
0
Order By: Relevance
“…This concept of linking fungal pathogenicity to damage was further supported by findings by Schönherr et al in which the virulence of C. albicans clinical isolates was directly correlated with their capacity to induce oral mucosal insult (44). Notably, only the expression of ECE1/Candidalysin was strongly correlated with damage and pathogenesis in several (but not all) C. albicans isolates.…”
Section: Figsupporting
confidence: 64%
“…This concept of linking fungal pathogenicity to damage was further supported by findings by Schönherr et al in which the virulence of C. albicans clinical isolates was directly correlated with their capacity to induce oral mucosal insult (44). Notably, only the expression of ECE1/Candidalysin was strongly correlated with damage and pathogenesis in several (but not all) C. albicans isolates.…”
Section: Figsupporting
confidence: 64%
“…Moreover, IL-1␣ plays a critical role in regulating host resistance in murine models of oral candidiasis (63,64). During oral candidiasis, IL-1␣ is secreted by keratinocytes (64). In contrast, we show that radiosensitive cells, including macrophages, are the major cellular source of IL-1␣ following A. fumigatus challenge (Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Specifically, the tongue epithelium is highly stratified. Schonherr and colleagues found that the depth of hyphal growth corresponds to IL-1␣ release in the candidiasis model (64). In contrast, the respiratory epithelium can be as thin as a single cell to facilitate gas exchange.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that the mutant strain does not differ from the wild‐type in initial settlement in the tongue but rather in its increased ability to persist in, and/or reduced clearance from, this tissue. The fast clearance of the reference strain in this OPC model is in agreement with previous reports (Conti et al ., ; Schönherr et al ., ). We confirmed that the phenotype of the mutant strain could be ascribed to the specified locus because adding back the corresponding wild‐type copy of the CUP9 gene to the deletion mutant strain resulted in reduced persistence (and/or more efficient clearance; Figure f).…”
Section: Resultsmentioning
confidence: 97%